Multiple sexual abuse among children in Kaduna State, North-western Nigeria: Does victim’s gender play a role? - Suleiman, Auwal G. (International Journal Of Community Medicine And Public Health, 2023)
Background: Child sexual abuse (CSA) is a human rights violation that affects millions of children globally. Many children continue to suffer sexual abuse, often due to non-disclosure of abuse. Disclosure is influenced by gender and the aim of this study was to assess whether gender was associated with multiple CSA experience. Methods: Data for this study came from a review of 420 medical reports retrieved from one of seven police area commands in Kaduna State, over a period of four years (2018-2021). Chi-square and Fisher’s exact tests were used to check for associations between multiple CSA experience and socio-demographic characteristics of the victims and their assailants at p value less than 0.05. Results: Among all victims, multiple CSA experience was significantly associated with male gender (χ2=11.99, p=0.001) and familiarity with assailant (χ2=13.63, p<0.001). Among male victims only, multiple CSA experience was not significantly associated with age of victim, familiarity with assailant, age of assailant or number of assailants (P>0.05). However, among female victims, multiple CSA experience was significantly associated with older age of victims (χ2=8.57, p=0.036), being familiar with the assailant (χ2=14.78, p<0.001) and older age of assailant (χ2 =8.13, p=0.017). Conclusions: Male gender was significantly associated with multiple CSA experience. Important associations between multiple CSA experience and socio-demographic characteristics of both the victims and their assailants were demonstrated among female but not male victims. More studies are needed to further understand these associations and provide recommendations.